Kedudukan Ine Ame dalam Upacara Adat Pemakaman di Desa Bareng Kecamatan Buyasuri Kabupaten Lembata: Studi Fenomenalogi dan Hukum Islam - Umi Kalsum; Jakaria M. Sali; Rahma Pramudya Nawang Sari; Nurhayati Natonis (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2024)
The traditional funeral ceremony involving ine ame is a funeral system that is still maintained and preserved. funeral system that is still maintained and continues to be preserved. In connection with this, the actions taken are real actions that are a form of respect for the deceased and his family. In Islamic law, the funeral process has been properly regulated such as informing the news of grief, bathing, shrouding, praying, burying. This research is an attempt to find out more about the traditional funeral ceremony found in the kedang community in bareng village, buyasuri sub-district, lembata district. This research uses a field research method with a qualitative descriptive approach. this research produces (1). The implementation process begins with informing the Ine Ame party, negotiating the ine ame party, luggage or kahalar, discussing customary fines such as Ote', belis, the attitude of the family, and finally reciprocity in the form of Atabelake. (2). The view of Islamic law regarding traditional funeral ceremonies This is a form of ceremony that can be said to be contrary to the provisions of Islamic law. Thus, it can be concluded that the traditional funeral ceremony in village of bareng, buyasuri sub-district, lembata district is contrary to Islamic law.